Challenges to Enterprise Performance in the Face of the Financial Crisis : Eastern Europe and Central Asia - World Bank (World Bank, 2012)
This report takes stock of enterprise sector performance in the Europe and Central Asia (ECA) region and its key drivers: access to finance, infrastructure, and labor. It is the second of two complementary reports that examine selected trends emerging from the Business Environment and Enterprise Performance Survey (BEEPS) data that are of immediate policy relevance to ECA countries. Both reports draw primarily on information from data collected prior to the crisis. This report also uses data on employment and access to finance collected during the crisis in a subset of ECA countries. The global financial crisis has had enormous consequences for firms' access to finance, the availability of qualified workers, and the ability of governments to provide (and of private sector to obtain) reliable infrastructure services. The extent and impact of these constraints is yet to be determined but their presence at a time of economic growth suggests they may re-emerge during the post-crisis economic recovery. The BEEPS captures information on a number of aspects of the business environment. This report highlights the elements of firm finance, labor regulations and skills, and infrastructure that are covered by the BEEPS questionnaire. Where possible, the data are supplemented with data from other sources. The report covers a lot of ground, and several broad findings from the analyses stand out.